Factors Influencing K-Pop Idol Fans' Compulsive Buying: The Role of K-pop Addiction, SNS Usage, Upward Social Comparison and Anxiety - Murti, Chyntia Dyahayu Wisnu; Wahyudi, Lilik; Brand, Human (Al-Makki Publisher, 2025)
The relationship between fans and K-pop Idol influence their consumption. Therefore, K-pop Idol categorized as a brand based on human brand theory. Moreover, digital era affects their lifestyle. This research aimed to assess K-pop Idol fans’ compulsive buying who use SNS in their daily activity. Survey responses were collected from an online sample of 268 K-pop idol fans in Indonesia. The methods were evaluated using software (smart PLS 3) to test the hypothesis. The authors found that, K-pop addiction, upward social comparison, anxiety level, and SNS usage have a direct effect on compulsive buying, this study also found that there is an indirect effect of K-pop addiction that mediates between SNS usage and compulsive buying. Future research should include psychological variables that can influence compulsive buying, use bigger sample, and focus on specific human brand. This paper provides insight for future brand marketing in Indonesia. This study can be said to be the first to examine the relationship between upward social comparison, SNS usage, anxiety level and K-pop addiction towards compulsive buying by referring the variable of brand addiction to K-pop addiction using Human Brand Theory by Thomson.